Genetic Ablation of MicroRNA-33 Attenuates Inflammation and Abdominal Aortic Aneurysm Formation via Several Anti-Inflammatory Pathways. Issue 11 (November 2017) - Nakao, Tetsushi; Horie, Takahiro; Baba, Osamu; Nishiga, Masataka; Nishino, Tomohiro; Izuhara, Masayasu; Kuwabara, Yasuhide; Nishi, Hitoo; Usami, Shunsuke; Nakazeki, Fumiko; Ide, Yuya; Koyama, Satoshi; et al.
Abstract : Objective—: Abdominal aortic aneurysm (AAA) is an increasingly prevalent and ultimately fatal disease with no effective pharmacological treatment. Because matrix degradation induced by vascular inflammation is the major pathophysiology of AAA, attenuation of this inflammation may improve its outcome. Previous studies suggested that miR-33 (microRNA-33) inhibition and genetic ablation of miR-33 increased serum high-density lipoprotein cholesterol and attenuated atherosclerosis. Approach and Results—: MiR-33a-5p expression in central zone of human AAA was higher than marginal zone. MiR-33 deletion attenuated AAA formation in both mouse models of angiotensin II– and calcium chloride–induced AAA. Reduced macrophage accumulation and monocyte chemotactic protein-1 expression were observed in calcium chloride–induced AAA walls in miR-33 −/− mice. In vitro experiments revealed that peritoneal macrophages from miR-33 −/− mice showed reduced matrix metalloproteinase 9 expression levels via c-Jun N-terminal kinase inactivation. Primary aortic vascular smooth muscle cells from miR-33 −/− mice showed reduced monocyte chemotactic protein-1 expression by p38 mitogen-activated protein kinase attenuation. Both of the inactivation of c-Jun N-terminal kinase and p38 mitogen-activated protein kinase were possibly because of the increase of ATP-binding cassette transporter A1 that is a well-known target of miR-33. Moreover, high-density lipoprotein cholesterol derived from miR-33 −/− mice reduced expression of matrix metalloproteinase 9 in macrophages and monocyte chemotactic protein-1 in vascular smooth muscle cells. Bone marrow transplantation experiments indicated that miR-33–deficient bone marrow cells ameliorated AAA formation in wild-type recipients. MiR-33 deficiency in recipient mice was also shown to contribute the inhibition of AAA formation. Conclusions—: These data strongly suggest that inhibition of miR-33 will be effective as a novel strategy for treating AAA. Abstract : Supplemental Digital Content is available in the text.